INCORPORATING BLENDED LEARNING APPROACH INTO THE INTENSIVE ENGLISH COURSE - I'Anatul Avifah (Universitas Teknokrat Indonesia, 2022)
The encompassing goal of the Intensive English Course at Universitas Billfath is to help students improve English skills so that they can pass the standardized English test. In practice, however, this expected goal could not be effectively achieved because of truancy issue and pandemic situation. In this scheme, blended learning is a thoughtful enhancement of learning experience with the incorporation of online technology which can offer flexibility of learning and social interaction to enhance learning. Moreover, as a kind of blended learning technology, a Virtual Learning Environment (VLE) can afford students with flexibility and opportunities to work collaboratively. Thus, this study is an attempt to propose an incorporation of blended learning approach into the existing classroom sessions in the Intensive English Course at Universitas Billfath. Since the proposed blended learning is a novel learning experience in this context, there may be several issues which remain significant to take into account. Further, it is also important to assess the effectiveness of the use of VLE in this blended learning design, so it warrants an evaluation to embark on the constructive review of how this kind of blend can enhance the English learning by developing its potentials and improving its imperfections.